ملاپازل ءِ’’پیاپیں‘‘چے گوش ایت؟ بن بزانتی بُن دروشمی وانشتے) - Baloch, Zia (Hanken, 2018)
This paper is based on the etymological study of the word “payáp”, which was first time used in the poetry of Mullah Fazil. Afterall, different poets used it in different meanings. In this paper, it is tried to search out the etyom and meaning from different texts and etymological dictionaries to find out the real meaning of this word.